Superconducting materials and their applications : an interdisciplinary approach - Yakhmi, J. V., 1946- (IOP Publishing, 2021)
The applications of superconducting materials have the potential to change our world, but descriptions of superconductivity in literature tend to be complex for non-physicists. This text provides an accessible account of superconductivity and its applications for an interdisciplinary readership. This book covers the characteristics of superconducting materials, particularly those with commercial applications, including MRI, MEG, high-field magnets, magnetometers, gradiometers, SQUID sensors and Josephson junctions. The applications and concepts are discussed at a level suitable for those with a basic background in physics, without using complex mathematics. This is a valuable reference text for researchers and practitioners working with devices made from superconducting materials. The text also acts as useful supplementary reading for courses related to superconductivity and superconducting materials.- Resumé vydavatel
Academic
Keywords: supravodivost; nauka o materiálu; superconductivity; materials science; elektronické knihy; monografie; electronic books; monographs